1995
DOI: 10.1111/j.1365-2621.1995.tb01948.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sporulation media and strain on thermal resistance of Bacillus cereus spores

Abstract: Spores of Bacillus cereus strains ATCC 7004, ATCC 4342 and ATCC 98 18 were produced in four sporulation media (Nutrient Agar supplemented with 1 ppm Mn2+, Fortified Nutrient Agar, Angelotti Medium and Milk Agar) and their percentages of sporulation and heat resistance parameters obtained in a wide temperature range were compared. In all conditions studied, high rates of sporulation were obtained. Clear differences among D-values for spores produced in the four media were observed. The medium which yielded the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 34 publications
5
24
1
2
Order By: Relevance
“…The thermal inactivation pattern of spores of B. cereus cultures observed in most of the earlier studies have revealed that D-values differ very much depending primarily on the strains used and to a lesser extent the extrinsic and intrinsic factors. Earlier studies have reported varying D-values for ATCC strains of B. cereus 4342, 7004 and 9818 in buffers and substrates similar to culture broth and those containing food constituents (Mazas et al 1995(Mazas et al , 1999aGonzález et al 1999;Montville et al 2005;Moussa-Boudjemma et al 2006). A similar situation was also reported for a strain of Bacillus anthracis Sterne (Novak et al 2005).…”
Section: Resultssupporting
confidence: 62%
“…The thermal inactivation pattern of spores of B. cereus cultures observed in most of the earlier studies have revealed that D-values differ very much depending primarily on the strains used and to a lesser extent the extrinsic and intrinsic factors. Earlier studies have reported varying D-values for ATCC strains of B. cereus 4342, 7004 and 9818 in buffers and substrates similar to culture broth and those containing food constituents (Mazas et al 1995(Mazas et al , 1999aGonzález et al 1999;Montville et al 2005;Moussa-Boudjemma et al 2006). A similar situation was also reported for a strain of Bacillus anthracis Sterne (Novak et al 2005).…”
Section: Resultssupporting
confidence: 62%
“…The differences between the D-values may be due to the differences in the test strains, inoculum levels, incubation temperatures, sporulation temperature, differences in nutrient composition and pH of the heating medium, water activity, presence or absence of divalent cations and antimicrobial compounds (Bahçeci and Acar, 2007). Similarly, Mazas et al (1995) determined the thermal resistance characteristics of B. cereus spores sporulated on different types of sporulation media (nutrient agar supplemented with Mn 2+ , fortified nutrient agar, Angelotti medium and milk agar). They found clear differences between the D-values for spores produced in the four media.…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic factors such as medium composition, sporulation temperature and water activity may influence spore properties (Gaillard et al 1998, González et al 1999, Palop et al 1999. The sporulation response to environmental conditions is species and strain specific (Mazas et al 1995, González et al 1999, sometimes even displaying opposite responses for the same factor, as reported for spores of different Bacillus species formed in rich and poor sporulation media (Baril et al 2012).…”
Section: Heat Resistance Of Biofilm Sporesmentioning
confidence: 95%
“…Sporulation temperature has a large effect on spore heat resistance of B. cereus with a 10 fold difference in decimal reduction time (D 100°C ) for spores formed at 20 compared to 45⁰C (González et al 1999). Most studies show lower impact of different factors such as sporulation medium, level of nutrients or pH on spore heat resistance, reporting between 1.3 to 6 fold changes in decimal reduction values (D-values) (Mazas et al 1995, Baweja et al 2008, Baril et al 2012). …”
Section: Heat Resistance Of Biofilm Sporesmentioning
confidence: 99%
See 1 more Smart Citation